THE INFLUENCE OF USING DIGITAL STORY TELLING AND MOTIVATION ON SPEAKING SKILL OF ELEVENTH- GRADE STUDENTS OF SMA NEGERI 1 SIMPANG - insana kamila; Indawan Syahri; Mulyadi Mulyadi (Universitas Muhammadiyah Makassar, 2021)
This research is to find out the influence of using digital storytelling and motivation on speaking skill of eleventh-grade students of SMA Negeri 1 Simpang. Out of 66 students, 34 students were selected as sample. The data were taken form questionnaire and oral test. This test was analyzed by using descriptive statistic, normality, homogeneity, pair sample t-test, independent sample t-test and two-way ANOVA. On tow way ANOVA result by SPSS 22, interaction’s score was 0.006 smaller than level of significant score was 0.05. For the result got interaction effect of Digital Storytelling and Motivation on student’s speaking ability. Based on data analysis, student’s speaking skill taught using Digital Storytelling approach increased significantly. Digital Storytelling was effective to improve student’s speaking skill in the experimental group.